2017
DOI: 10.3389/fphar.2017.00554
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin Modulates HCN4 Channel Voltage-Dependence

Abstract: Gabapentin (GBP) is widely used to treat epilepsy and neuropathic pain. There is evidence that GBP can act on hyperpolarization-activated cation (HCN) channel-mediated Ih in brain slice experiments. However, evidence showing that GBP directly modulates HCN channels is lacking. The effect of GBP was tested using two-electrode voltage clamp recordings from human HCN1, HCN2, and HCN4 channels expressed in Xenopus oocytes. Whole-cell recordings were also made from mouse spinal cord slices targeting either parvalbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…The final version may differ from this version. Gabapentin has also been found to augment KATP currents in rat hippocampal and human neocortical slices (but not incidentally, in rat DRG neurons) (Freiman et al, 2001), and to inhibit the hyperpolarization-activated, cyclic nucleotide-gated channel, HCN4, albeit not at clinically relevant drug concentrations (Tae et al, 2017). Conversely, gabapentin augmented in hippocampal and inhibitory interneurons, cells that highly express HCN1 and HCN2 (Peng et al, 2011;Surges et al, 2003).…”
Section: Multiple Gabapentinoid Targets In Neurons -A Role For Kcnqs?mentioning
confidence: 99%
“…The final version may differ from this version. Gabapentin has also been found to augment KATP currents in rat hippocampal and human neocortical slices (but not incidentally, in rat DRG neurons) (Freiman et al, 2001), and to inhibit the hyperpolarization-activated, cyclic nucleotide-gated channel, HCN4, albeit not at clinically relevant drug concentrations (Tae et al, 2017). Conversely, gabapentin augmented in hippocampal and inhibitory interneurons, cells that highly express HCN1 and HCN2 (Peng et al, 2011;Surges et al, 2003).…”
Section: Multiple Gabapentinoid Targets In Neurons -A Role For Kcnqs?mentioning
confidence: 99%
“…This would predict additional mechanisms of Drugs for Neuropathic Pain gabapentinoid effectiveness. For example, gabapentin has been reported to shift the voltage dependence of HCN4 channels to more negative potentials (Tae et al, 2017), but may increase hyperpolarization-activated cation current in hippocampal neurons (Surges et al, 2003). It has also been reported to interact with NMDA and AMPA receptors, as well as K ATP channels (Cheng and Chiou, 2006).…”
mentioning
confidence: 99%
“…Most notably, both excitatory and inhibitory PV-neurons in the LTMR-RZ exhibit tonic firing and the voltage sag (a slowly developing depolarization during hyperpolarizing current injection), which is generated by the activation of I h upon hyperpolarization [ 28 ]. Although Tae et al (2017) recorded I h in putative inhibitory neurons that expressed GFP driven by the PV promoter, they also demonstrated that Pax2 (a marker of inhibitory neurons) did not colocalize with HCN4 [ 35 ]. Furthermore, we found that almost all HCN4-IR neurons lacked fluorescent proteins in VGAT-Venus or GAD67-GFP mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For the same rationale, HCN channels may antagonize the hyperpolarization of PKCγ-IR interneurons induced by the activity of inhibitory interneurons. HCN channels expressed in the spinal cord, as well as in the PNS, may be potential therapeutic targets of allodynia [ 35 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%